JURIDICAL ANALYSIS OF THE CRIME OF MALTREATMENT RESULTING IN SERIOUS INJURY - Alice; Bonggoibo (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
Persecution is a crime committed by intentionally damaging the health of another person resulting in injury or pain to a person's body, this persecution is also usually carried out because of a grudge or feeling humiliated by others persecution. the problem of persecution and the Judges' Legal Considerations in imposing crimes against perpetrators of persecution in the Manokwari District Court Decision No. 149/Pid.B.2021.PN.MNK. The purpose of this research is to find out the provisions referred to in the crime of maltreatment of serious injury and to find out the application of criminal sanctions against victims of maltreatment causing serious injury with case number 149/Pid.B.2021.PN.MNK). The method of analysis and the data obtained are analyzed qualitatively, namely the analysis carried out by understanding and assembling legal materials related to the problems that have been collected descriptively so that an overview of the problem under study can be obtained, then the legal material is presented systematically and then legal interpretation is carried out.